Crystallite size induced bandgap tuning in WO3 derived from nanocrystalline tungsten. (February 2020) - Bandi, Suresh; Vidyasagar, Devthade; Adil, Shaik; Singh, Manish Kumar; Basu, Joysurya; Srivastav, Ajeet K.
Abstract: In this work, nanocrystalline tungsten oxide (WO3 ) powder was obtained by high energy ball milling (HEBM) followed by heat treatment of tungsten (W) powder. HEBM significantly influenced the oxidation behavior by reducing the crystallite size and inducing lattice strain in W powder. The resultant nanocrystalline WO3 shows variation in the optical bandgap with respect to the bulk counterparts. The alteration in the bandgap of WO3 is ascribed to the changes in crystallite size and the unit cell volume. In the end, a thorough correlation between fundamental interactions of these changes was succinctly highlighted. Graphical abstract: Image, graphical abstract